Forming method of super-crosslinked phosphine ligand polymer Rh catalyst, formed catalyst and application of formed catalyst

Through the molding method of supercrosslinked phosphine ligand polymer supported rhodium catalyst, the problem of catalyst swelling in the hydroformylation reaction of allyl acetate is solved, and efficient catalyst recovery and reuse is achieved, reducing production costs.

CN119746938APending Publication Date: 2025-04-04QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411797681.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, there is a problem of catalyst swelling in the hydroformylation reaction of allyl acetate, resulting in damage to the catalyst structure and loss of metal active centers, thereby reducing catalytic activity and increasing production safety risks.

Method used

The molding method of supercrosslinked phosphine ligand polymer supported rhodium catalyst is adopted. By mixing with an inert substance and slowly adding a liquid glue solution, forming a mixed material, drying and grinding, and finally tableting is performed with a tablet press to obtain a molding catalyst with high mechanical strength and long-term catalytic activity.

Benefits of technology

It effectively solves the problem of catalyst swelling, maintains the long-term activity and mechanical strength of the catalyst, and realizes efficient catalysis of the hydroformylation reaction of allyl acetate, and the catalyst can be recycled and reused, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746938A_ABST
    Figure CN119746938A_ABST
Patent Text Reader

Abstract

The invention discloses a forming method of a super-crosslinked phosphine ligand polymer Rh catalyst, a formed catalyst prepared by the method and application of the catalyst. The method comprises the following steps: 1) mixing a hypercrosslinked phosphine ligand polymer Rh catalyst with an inert substance, and slowly dropwise adding a liquid glue solution in the mixing process to obtain a mixed material; 2) drying the obtained mixed material to obtain a dried catalyst; and 3) fully grinding the dried catalyst, tabletting with a tablet press, and sieving with a 20-40-mesh sieve to obtain the formed catalyst. The formed catalyst prepared according to the forming method solves the problem of swelling property of the catalyst, can be applied to a fixed bed reactor for a long time, basically has no metal loss, is beneficial to subsequent separation and purification, and has better selectivity of linear aldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst molding, and in particular relates to a molding method of a super-crosslinked phosphine ligand polymer Rh catalyst, a molded catalyst prepared by the method, and use of the catalyst. Background Art

[0002] Transition metal-catalyzed hydroformylation of olefins containing functional groups is one of the most important reactions in industry and organic synthesis, and is a good method for synthesizing bifunctional compounds. In particular, using allyl acetate, which is readily available in industry, as a raw material is an attractive synthetic route for preparing bifunctional compounds. The acetaldehyde compounds obtained by hydroformylation of allyl acetate can be further converted into 1,3 and 1,4-butanediol, which have a wide range of applications as polymer raw material monomers.

[0003] 1,4-Butanediol (BDO) is one of the most important chemicals in the chemical industry. As a starting material, it is used to produce chemicals such as γ-butyrolactone and tetrahydrofuran; as a monomer, it is used to produce biodegradable plastic materials, including polybutylene terephthalate (PBT) and polybutylene adipate (PBAT). Therefore, 1,4-butanediol can be widely used in the pharmaceutical, chemical and material fields. Using allyl acetate as a starting material through hydroformylation technology is an effective solution to replace the current traditional process for producing BDO. The reaction process involves two steps of hydroformylation and hydrogenation, of which the first step, allyl acetate hydroformylation, determines the overall efficiency of the process.

[0004] In recent years, the use of homogeneous rhodium-phosphine complex catalysts (J. Chem. Soc., Chem. Commun., 1993, 316-317; J. Mol. Catal. A: Chem. 1996, 17-23; Mol. Catal. 2023, 113209; Catal. Lett. 2024, 15, 5163-5170) for the hydroformylation of allyl acetate has made good progress, but there is a problem that the expensive Rh-phosphine complex is difficult to recover and recycle. At the same time, allyl acetate has a variety of competitive side reactions during the hydroformylation reaction, such as hydrogenation reaction and decomposition reaction, resulting in poor chemical selectivity of the reaction. In addition, allyl acetate is a functional olefin, and the oxygen atom of the ester group of allyl acetate is easy to form a thermodynamically stable six-membered ring transition state with the metal center during the hydroformylation reaction, resulting in the reaction mainly generating branched products. Currently, there are few reports on the efficient and highly regioselective synthesis of 4-acetoxybutyraldehyde from allyl acetate using stable heterogeneous catalysts, which is challenging.

[0005] In recent years, hypercrosslinked polymers (HCPs) have become a promising class of organic polymer carriers due to their many advantages, including inherent porosity, high surface area, cost-effectiveness, and ease of functionalization. Hypercrosslinked polymers have been widely used to load metals to form heterogeneous catalysts to achieve a variety of organic transformations. Although the metal heterogeneous catalysts based on hypercrosslinked polymers show relatively ideal activity and selectivity in several important organic transformation reactions, and can achieve simple separation and recycling of catalysts and products. However, the network organic molecular skeleton units in the hypercrosslinked polymers are prone to swelling in organic solvents, especially under reaction conditions (such as a certain reaction temperature, reaction pressure, etc.), resulting in the destruction of the catalyst structure (such as collapse) and the leaching of metal active centers (such as falling off or loss), which in turn leads to a decrease in catalyst activity or even inactivity. It should be pointed out that the swelling problem can cause the catalyst to block the reaction pipeline during the use of the fixed bed reactor, posing a potential safety hazard in production. Therefore, developing a catalyst that can effectively overcome the stability problems such as catalyst deactivation caused by swelling is one of the key issues that urgently need to be solved in the application of hypercrosslinked loaded metals. Summary of the invention

[0006] In view of the problems in the above-mentioned prior art, the present invention successfully developed a method for forming a hyper-crosslinked phosphine ligand polymer (HCP) loaded with rhodium catalyst, which can effectively maintain the long-term catalytic activity and high mechanical strength of the catalyst, and can efficiently catalyze the hydroformylation reaction of allyl acetate to prepare 4-acetoxybutyraldehyde with higher added value, and can realize the recovery and reuse of the catalyst after the reaction is completed, avoiding the loss of metals and ligands, and having good cyclic catalytic performance, which can greatly reduce production costs. At the same time, the present invention also develops a hyper-crosslinked phosphine ligand polymer Rh prepared by the molding method and the use of the catalyst in a fixed bed reactor.

[0007] According to one aspect of the present invention, one of the objects of the present invention is to provide a method for forming a hyper-crosslinked phosphine ligand polymer (HCP) Rh catalyst, comprising the following steps:

[0008] 1) mixing the hyper-crosslinked phosphine ligand polymer Rh catalyst with an inert substance, and then slowly adding a liquid glue solution dropwise during the mixing process to obtain a mixed material;

[0009] 2) drying the obtained mixed material to obtain a dried catalyst;

[0010] 3) Grind the dried catalyst fully, compress it into tablets using a tablet press, and pass it through a 20-40 mesh sieve to obtain a molded catalyst.

[0011] Preferably, in step 1), the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance are first mixed for 10-60 minutes, and then the liquid glue solution is added dropwise and the mixing is continued for 0.5 to 2 hours, more preferably 1 to 1.5 hours.

[0012] Preferably, the inert substance in step 1) is one or more of silicon powder, alumina and molecular sieve.

[0013] Preferably, the mass of the inert substance in step 1) is 20 to 80 wt % of the total mass of the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance.

[0014] Preferably, the liquid glue in step 1) is an aqueous solution selected from the following substances: one or more of polyvinyl alcohol, polyacrylate, polyalkyl acrylate, preferably polyvinyl alcohol, and the concentration is preferably 0.1-10wt%, more preferably 0.3-5wt%, more preferably 0.3-1.6wt%.

[0015] Preferably, the weight average molecular weight of the polyvinyl alcohol is preferably 400 to 20,000, more preferably 1,000 to 15,000, and most preferably 5,000 to 10,000. When the weight average molecular weight of the polyvinyl alcohol is lower than 400 or higher than 20,000, the swelling problem of the polymer in the catalyst cannot be effectively prevented, and thus the problem of catalyst "expansion" and blockage in the fixed bed reactor cannot be effectively solved.

[0016] Preferably, in the mixed material in step 1), the ratio of the mass of water to the total mass of the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance is (0.2-0.4):1.

[0017] Preferably, the drying in step 2) is specifically: first drying at 20-50° C. for 12-36 hours, and then drying at 50-80° C. for 3-18 hours.

[0018] According to one aspect of the present invention, one of the objects of the present invention is to provide a shaped super-crosslinked phosphine ligand polymer Rh catalyst obtained according to the shaping method.

[0019] According to one aspect of the present invention, one of the purposes of the present invention is to provide the use of the shaped super-crosslinked phosphine ligand polymer Rh catalyst in a fixed bed reactor to catalyze the hydroformylation of allyl acetate to prepare 4-acetoxybutyraldehyde.

[0020] Preferably, the catalyst is loaded after being diluted with porcelain balls, the volume percentage of the catalyst in the total loading is 70% to 90%, the inlet pressure of the reaction gas is 1-8Mpa, the reaction gas is a mixed gas of hydrogen and carbon monoxide, and the absolute volume space velocity of allyl acetate to the catalyst is 10 to 200h-1 , the inlet concentration of allyl acetate is 6% to 12% mol / L, the molar ratio of toluene to allyl acetate is 1 to 2, and the reaction temperature is 50 to 200°C.

[0021] Preferably, the fixed bed reactor is divided into three reaction zones, namely, an upper section, a middle section and a lower section from top to bottom, the proportion of the catalyst increases successively, and the catalyst loading amounts of the three sections are in a weight ratio of 1:2:3.

[0022] Beneficial Effects

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] The molded catalyst prepared by the molding method of the present invention solves the problem of catalyst swelling, can be used for a long time in a fixed bed reactor, has substantially no metal loss, is beneficial to subsequent separation and purification, and has better selectivity for linear aldehydes. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 The long-term evaluation results of the catalyst of Example 3;

[0027] Figure 2 This is the adsorption analysis curve of the catalyst in Example 3.

[0028] Figure 3 This is the pore size distribution diagram of the catalyst of Example 3.

[0029] Figure 4 This is a scanning electron microscope image of the catalyst of Example 3.

[0030] Figure 5 This is a transmission electron microscopy image of the catalyst of Example 3. DETAILED DESCRIPTION

[0031] Hereinafter, the present invention will be described in detail. Before describing, it should be understood that the terms used in this specification and the appended claims should not be interpreted as being limited to the general meaning and dictionary meaning, but should be interpreted according to the meaning and concept corresponding to the technical aspects of the present invention on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, the descriptions presented here are only preferred examples for illustrative purposes and are not intended to limit the scope of the present invention, so that it should be understood that other equivalents or improvements can be obtained therefrom without departing from the spirit and scope of the present invention.

[0032] In this document, the terms "include", "including", "have", "contain" or any other similar terms are open conjunctions, which are intended to cover non-exclusive inclusions. For example, a composition or product containing multiple elements is not limited to the elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or product. In addition, unless otherwise explicitly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and A and B are both true (or exist). In addition, in this document, the interpretation of the terms "include", "including", "have", and "contain" should be considered to have been specifically disclosed and simultaneously cover closed or semi-closed conjunctions such as "consisting of" and "consisting essentially of".

[0033] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values ​​within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all secondary ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially secondary ranges defined by all integer values, and should be deemed to have specifically disclosed individual values ​​such as 1, 2, 3, 4, 5, 6, 7, 8, etc. within the range. Unless otherwise specified, the above interpretation method applies to all contents of the entire present invention, regardless of whether the range is broad or not.

[0034] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether these ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0035] In this document, under the premise of achieving the purpose of the invention, numerical values ​​should be understood to have the accuracy of the number of significant digits of the numerical value. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.

[0036] The present invention provides a method for forming a hyper-crosslinked phosphine ligand polymer-supported rhodium catalyst, comprising the following steps:

[0037] 1) firstly mixing the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance for 10-60 minutes, then slowly adding the liquid glue solution dropwise, and continuing to mix for 0.5-2 hours, more preferably 1-1.5 hours, to obtain a mixed material;

[0038] 2) drying the obtained mixed material to obtain a dried catalyst;

[0039] 3) Grind the dried catalyst fully, compress it into tablets using a tablet press, and pass it through a 20-40 sieve to obtain a molded catalyst.

[0040] The molding method in the present invention has a wide adaptability to the hyper-crosslinked phosphine ligand polymer Rh catalyst. The present invention does not impose any special restrictions on the specific type or composition of the hyper-crosslinked phosphine ligand polymer Rh catalyst. In the present invention, the hyper-crosslinked phosphine ligand polymer Rh catalyst can be a conventional hyper-crosslinked phosphine ligand polymer Rh catalyst in the art, or a commercially available hyper-crosslinked phosphine ligand polymer Rh catalyst.

[0041] In the present invention, the inert substance is preferably one or more of silica gel, alumina, and molecular sieves; preferably, the total mass of the hyper-crosslinked phosphine ligand polymer-supported rhodium catalyst and the inert substance is 20 to 80 wt%, more preferably 25 to 35 wt%, such as 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0042] According to the step 1) of the molding method of the present invention, the liquid glue is an aqueous solution selected from the following substances: polyvinyl alcohol, polyacrylate, polyalkyl acrylate, preferably polyvinyl alcohol, and the concentration is preferably 0.1-10wt%, more preferably 0.3-5wt%, more preferably 0.3-1.6wt%, such as 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 5wt%, 8wt%, 10wt%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0043] Preferably, the liquid glue in step 1) is an aqueous solution selected from the following substances: one or more of polyvinyl alcohol, liquid butadiene benzene and liquid styrene-butadiene-styrene block copolymer (SBS), preferably polyvinyl alcohol, and the concentration is preferably 0.1-10wt%, more preferably 0.3-5wt%, more preferably 0.3-1.6wt%. Preferably, in the mixed material in step 1), the ratio of the mass of water to the total mass of the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance is (0.2-0.4):1.

[0044] Preferably, the weight average molecular weight of the polyvinyl alcohol is preferably 400 to 20,000, more preferably 1,000 to 15,000, and most preferably 5,000 to 10,000. When the weight average molecular weight of the polyvinyl alcohol is lower than 400 or higher than 20,000, the swelling problem of the polymer in the catalyst cannot be effectively prevented, and thus the problem of catalyst "expansion" and clogging in the fixed bed reactor cannot be effectively solved. In the present invention, the mixed material is preferably pressed into tablets, and then the formed catalyst is dried to obtain a dried catalyst.

[0045] The present invention also provides the use of the shaped super-crosslinked phosphine ligand polymer Rh catalyst in a fixed bed reactor to catalyze the hydroformylation of allyl acetate to prepare 4-acetoxybutyraldehyde, wherein the inner diameter of the fixed bed reactor used in the reaction is 24-26 mm, the loading amount of the catalyst is 4-6 g, the catalyst is diluted with porcelain balls and then loaded, and the volume percentage of the catalyst in the total loading amount is 70% to 90%, more preferably 75-85%, such as 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0046] In the present invention, the inlet pressure of the reaction gas of the fixed bed reactor is preferably 1-8 MPa, more preferably 1-5 MPa, such as 1 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, preferably 1 MPa, 2 MPa, 3 MPa. The range value is a value with any of the above values ​​as the upper or lower limit.

[0047] The reaction gas is a mixture of hydrogen and carbon monoxide, and the absolute volume space velocity of allyl acetate to the catalyst is preferably 10 to 200 h -1 , more preferably 150 to 200 hours -1 , such as 100h -1 , 150h -1 、180h -1 , 190h -1 , 200h-1 , preferably a range value with any of the above numerical values ​​as the upper or lower limit.

[0048] In the reaction gas, the inlet concentration of allyl acetate is preferably 6% to 12% mol / L, more preferably 7 to 11%, such as 6%, 7%, 8%, 9%, 10%, 11%, 12%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0049] The molar ratio of allyl acetate to toluene is preferably 0.8-3:1, more preferably 1-2.5, such as 0.8:1, 0.9:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, preferably a range value with any of the above values ​​as the upper or lower limit.

[0050] The reaction temperature is preferably 50-200°C, more preferably 100-180°C, such as 100°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, preferably a range with any of the above values ​​as the upper or lower limit.

[0051] The following examples are only listed as examples of embodiments of the present invention and do not constitute any limitation to the present invention. It can be understood by those skilled in the art that modifications within the scope of the essence and concept of the present invention fall within the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products.

[0052] Preparation of raw powder catalyst:

[0053] Example 1: Preparation of hyper-crosslinked phosphine ligand polymer HCP-2.5

[0054] Under argon protection, 200 mg of compound 1,2-bis(diphenylphosphino)ethane, 168 mg of compound phenol and 15 mg of tert-butyl peroxide were added to a reaction bottle, 5 mL of THF was added to dissolve, and the mixture was reacted at 80°C for 48 h. The mixture was cooled to room temperature, methanol was added to disperse the mixture, filtered and dried to obtain 330 mg of super-crosslinked phosphine ligand polymer HCP.

[0055] Forming catalyst preparation:

[0056] Example 2: Preparation of hyper-crosslinked phosphine ligand polymer HCP supported rhodium catalyst Rh@HCP-2.5

[0057] Under argon protection, 123 mg of the hyper-crosslinked phosphine ligand polymer HCP-2.5 prepared in Example 1 was dispersed in 5 mL of tetrahydrofuran, and 26 mg of Rh4(CO) was added. 12, stirred at room temperature for 24 hours, and the solvent was removed under reduced pressure to obtain 112 mg of hyper-crosslinked phosphine ligand polymer HCP loaded rhodium-based catalyst. Silicon powder was mixed with the original powder catalyst in an amount of 20 wt% of the total solid content of the catalyst for 60 minutes, that is, 100 mg of silicon powder was added to 500 mg of the original powder catalyst, and then polyvinyl alcohol (weight average molecular weight of 8000) aqueous solution (3.0 wt%) was slowly added dropwise. After the addition was completed, the mixing was continued for 0.5 to 2 hours, and then the formed catalyst was dried, and the mixed material was pressed into tablets. Drying is preferably air drying or vacuum drying, first drying at 40°C for 24 hours, and then drying at 70°C for 12 hours.

[0058] Example 3

[0059] 2 g of ground 3A molecular sieve was added during kneading, and the mixture was kneaded for 1 h. Subsequently, 5 mL of tartaric acid solution with a mass concentration of 16.7% was added, and the mixture was kneaded for 40 min. The other preparation conditions were the same as those in Example 2.

[0060] Comparative Example 1

[0061] No polyvinyl alcohol was added during the kneading process, and the remaining processes were the same as in Example 2. Strips could be produced during the extrusion process, but the plasticity of the powder was poor, and the extruded strip catalyst had poor elasticity, a rough surface, and could not be pressed into tablets.

[0062] Comparative Example 2

[0063] No inert material was added during the kneading process, and the remaining process was the same as in Example 2, and no molding could be performed.

[0064] Comparative Example 3

[0065] During the kneading process, only polyvinyl alcohol was added without adding water. The remaining process was the same as in Example 2, and tableting could not be performed.

[0066] Comparative Example 4

[0067] A catalyst was prepared in the same manner as in Example 3 except that polyvinyl alcohol with a weight average molecular weight of 300 was used.

[0068] Comparative Example 5

[0069] A catalyst was prepared in the same manner as in Example 3 except that polyvinyl alcohol having a weight average molecular weight of 30,000 was used.

[0070] Table 1 Strength data of the molded catalysts obtained in the examples and comparative examples

[0071] catalyst Strength N / cm Remark Example 1 80 Unable to form tablets Example 2 92 Poor stability Example 3 110 Capable of forming Comparative Example 1 45 Unable to form tablets Comparative Example 2 38 Unable to form tablets Comparative Example 3 29 Unable to form tablets Comparative Example 4 90 Poor stability Comparative Example 5 243 Capable of forming

[0072] It can be seen from Table 1 that under the preparation conditions given in the present invention, the crushing strength of the catalyst is greater than 80 N / cm. When the amount of molding aid added is high, the pore expansion is obvious and the strength is high. In Comparative Example 1, the failure to add polyvinyl alcohol will lead to tableting failure. In Comparative Example 2, the failure to add inert substances will result in very low catalyst strength, leading to tableting failure. In Comparative Example 3, no water is added, which will also lead to poor strength and difficulty in molding.

[0073] Application Example 1

[0074] The catalyst of Example 2 was first loaded with 6 mL of porcelain balls at the bottom of the reactor for support, 2.5 mL of catalyst was mixed with 3 mL of porcelain balls and then loaded into the reactor as the lower reaction zone, 2 mL of catalyst was mixed with 2 mL of porcelain balls and then loaded into the reactor as the middle reaction zone, 1 mL of catalyst was mixed with 1.5 mL of porcelain balls and then loaded into the reactor as the upper reaction zone, and finally 5 mL of porcelain balls were loaded into the reactor as the preheating zone of the reaction gas. The proportions of the catalyst in the three reaction zones from top to bottom were 17%, 33%, and 46%, respectively, and the tubular reactor was heated. The temperature was heated to 150°C, the inlet pressure was maintained at 2 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0075] Application Example 2

[0076] The catalyst of Example 3 was loaded into a tubular reactor with an inner diameter of 26 mm, with a catalyst loading of 6 mL. It was diluted with 3 mm porcelain balls, and the total volume of the porcelain balls was 6.5 mL. First, 6 mL of porcelain balls were loaded at the bottom of the reactor for bottoming. 2.5 mL of catalyst was mixed with 3 mL of porcelain balls and loaded into the reactor as the lower reaction zone. 2 mL of catalyst was mixed with 2 mL of porcelain balls and loaded into the reactor as the middle reaction zone. 1 mL of catalyst was mixed with 1.5 mL of porcelain balls and loaded into the reactor as the upper reaction zone. Finally, 5 mL of porcelain balls were loaded as the preheating zone of the reaction gas. The proportions of catalysts in the three reaction zones from top to bottom were 17%, 33%, and 46%, respectively. The tubular reactor was heated. The temperature was heated to 150°C, the inlet pressure was maintained at 2 MPa, and the absolute air velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0077] Application Example 3

[0078] The catalyst of Example 3 was loaded into a tubular reactor with an inner diameter of 26 mm, with a catalyst loading of 6 mL. It was diluted with 3 mm porcelain balls, and the total volume of the porcelain balls was 6.5 mL. First, 6 mL of porcelain balls were loaded at the bottom of the reactor for bottoming. 2.5 mL of catalyst was mixed with 3 mL of porcelain balls and loaded into the reactor as the lower reaction zone. 2 mL of catalyst was mixed with 2 mL of porcelain balls and loaded into the reactor as the middle reaction zone. 1 mL of catalyst was mixed with 1.5 mL of porcelain balls and loaded into the reactor as the upper reaction zone. Finally, 5 mL of porcelain balls were loaded as the preheating zone of the reaction gas. The proportions of catalysts in the three reaction zones from top to bottom were 17%, 33%, and 46%, respectively. The tubular reactor was heated. The temperature was heated to 150°C, the inlet pressure was maintained at 2 MPa, and the absolute air velocity of allyl acetate was 200 h -1 , inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0079] Application Example 4

[0080] The catalyst of Example 3 was loaded into a tubular reactor with an inner diameter of 26 mm, with a catalyst loading of 6 mL. It was diluted with 3 mm porcelain balls, and the total volume of the porcelain balls was 6.5 mL. First, 6 mL of porcelain balls were loaded at the bottom of the reactor for bottoming. 2.5 mL of catalyst was mixed with 3 mL of porcelain balls and loaded into the reactor as the lower reaction zone. 2 mL of catalyst was mixed with 2 mL of porcelain balls and loaded into the reactor as the middle reaction zone. 1 mL of catalyst was mixed with 1.5 mL of porcelain balls and loaded into the reactor as the upper reaction zone. Finally, 5 mL of porcelain balls were loaded as the preheating zone of the reaction gas. The proportions of catalysts in the three reaction zones from top to bottom were 17%, 33%, and 46%, respectively. The tubular reactor was heated. The temperature was heated to 150°C, the inlet pressure was maintained at 2 MPa, and the absolute air velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0081] Application Example 5

[0082] The catalyst of Example 3 was loaded into a tubular reactor with an inner diameter of 26 mm, with a catalyst loading of 6 mL. It was diluted with 3 mm porcelain balls, and the total volume of the porcelain balls was 6.5 mL. First, 6 mL of porcelain balls were loaded at the bottom of the reactor for bottoming. 2.5 mL of catalyst was mixed with 3 mL of porcelain balls and loaded into the reactor as the lower reaction zone. 2 mL of catalyst was mixed with 2 mL of porcelain balls and loaded into the reactor as the middle reaction zone. 1 mL of catalyst was mixed with 1.5 mL of porcelain balls and loaded into the reactor as the upper reaction zone. Finally, 5 mL of porcelain balls were loaded as the preheating zone of the reaction gas. The proportions of catalysts in the three reaction zones from top to bottom were 17%, 33%, and 46%, respectively. The tubular reactor was heated. The temperature was heated to 150°C, the inlet pressure was maintained at 2 MPa, and the absolute air velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0083] Application Example 6

[0084] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 140°C, the inlet pressure was maintained at 2 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0085] Application Example 7

[0086] The catalyst of Example 2 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 160°C, the inlet pressure was maintained at 2 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0087] Application Example 8

[0088] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 1 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0089] Application Example 9

[0090] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1, the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0091] Application Example 10

[0092] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 100 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0093] Application Example 11

[0094] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 300 h -1 , the inlet allyl acetate concentration is 9% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0095] Application Example 12

[0096] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 5% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0097] Application Example 13

[0098] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 12% mol / L, the molar ratio of allyl acetate to toluene is 1.5:1, and the mixed gas velocity is 1 L / h.

[0099] Application Example 14

[0100] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 5% mol / L, the molar ratio of allyl acetate to toluene is 1:1, and the mixed gas velocity is 1 L / h.

[0101] Application Example 15

[0102] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , the inlet allyl acetate concentration is 5% mol / L, the molar ratio of allyl acetate to toluene is 2:1, and the mixed gas velocity is 1 L / h.

[0103] Application Example 16

[0104] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , inlet allyl acetate concentration 5% mol / L, allyl acetate to toluene ratio 1.5:1, mixed gas velocity 0.5 L / h.

[0105] Application Example 17

[0106] The catalyst of Example 3 was loaded into the reactor in the same manner as in Application Example 2. The temperature was heated to 150°C, the inlet pressure was maintained at 3 MPa, and the absolute space velocity of allyl acetate was 200 h -1 , inlet allyl acetate concentration 5% mol / L, allyl acetate to toluene ratio 1.5:1, mixed gas velocity 1.5 L / h.

[0107] Comparative application example 1

[0108] The pure catalyst of Example 1 was loaded into the reactor, and the reaction conditions were the same as those of Application Example 10. The results showed that a surge in pressure occurred at the beginning of the reaction, and the reaction was forced to stop.

[0109] Comparative Application Example 2

[0110] The catalyst of Example 3 was loaded into the reactor without adding porcelain balls, and the reaction conditions were the same as those of Application Example 10. A surge in pressure occurred at the beginning of the reaction, and the reaction was forced to stop.

[0111] Comparative Application Example 3

[0112] Except for the catalyst prepared in Comparative Example 4, the application test was carried out in the same manner as in Application Example 2.

[0113] Comparative Application Example 4

[0114] Except for the catalyst prepared in Comparative Example 5, the application test was carried out in the same manner as in Application Example 2.

[0115] Table 2. Single tube evaluation results of catalysts

[0116]

[0117]

[0118] It can be seen from Table 2 that in a wide range of allyl acetate air velocity (100~300h -1 ), the catalyst maintained a high allyl acetate conversion rate and 4-acetoxybutyraldehyde selectivity, allyl acetate conversion rate>75.3%, 4-acetoxybutyraldehyde selectivity>76.2%. Different loading methods have a great influence on the conversion rate and selectivity of allyl acetate. For example, from Application 1 to Application 5, it can be seen that according to the loading method of Application Example 2, the conversion rate and selectivity of allyl acetate reached the highest value among the five application examples. Under the loading method of Application Example 2, the temperature is changed. According to Table 2, it can be seen that at 150°C, the reaction effect is the best, the allyl acetate conversion rate is 92.3%, and the 4-acetoxybutyraldehyde selectivity is 95.4%. Under the loading method of Application Example 2, the pressure is changed. According to Table 2, it can be seen that at 3Mpa, the reaction effect is the best, the allyl acetate conversion rate is 95.3%, and the 4-acetoxybutyraldehyde selectivity is 97.4%. Under the loading method of Application Example 2, the pressure is changed. According to Table 2, it can be seen that the flow rate is 200h -1 Under the filling method of Application Example 2, the reaction effect is the best, the conversion rate of allyl acetate is 95.3%, and the selectivity of 4-acetoxybutyraldehyde is 97.4%. Under the filling method of Application Example 2, the concentration of allyl acetate is changed. According to Table 2, it can be seen that the reaction effect is best when the concentration is 5% mol / L, the conversion rate of allyl acetate is 98.3%, and the selectivity of 4-acetoxybutyraldehyde is 98.4%. Under the filling method of Application Example 2, the molar ratio of allyl acetate and toluene is changed. According to Table 2, it can be seen that when the molar ratio is 1.5:1, the reaction effect is the best, the conversion rate of allyl acetate is 98.3%, and the selectivity of 4-acetoxybutyraldehyde is 98.4%. Under the filling method of Application Example 2, the mixed gas velocity is changed. According to Table 2, it can be seen that when the mixed gas velocity is 1L / h, the reaction effect is the best, the conversion rate of allyl acetate is 98.6%, and the selectivity of 4-acetoxybutyraldehyde is 98.9%. If the original powder catalyst is directly loaded into the reactor, such as in comparative application example 1, a surge occurs and the reaction cannot be normal; if the catalyst is directly loaded into the reactor without being diluted by an inert porcelain ball, such as in comparative application example 2, a surge occurs and the reaction cannot be normal. If the weight average molecular weight of the adhesive component polyvinyl alcohol used is too small, for example, 300, such as in comparative application example 3, although the catalyst can be formed, the stability is not good, and long-term operation will still cause a surge (the main reason is the blockage of the reaction channel), and the reaction cannot be normal. If the weight average molecular weight of the adhesive component polyvinyl alcohol used is too large, for example, 30,000, such as in comparative application example 4, although the catalyst has a high degree of formation, due to the excessive molecular weight of the polyvinyl alcohol used, its molecular structure is too rigid, causing the catalyst active component to be unable to fully contact the reaction material, thereby reducing the catalytic performance, resulting in poor conversion rate and selectivity of allyl acetate.

[0119] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for forming a hyper-crosslinked phosphine ligand polymer Rh catalyst, comprising the following steps: 1) mixing the hyper-crosslinked phosphine ligand polymer Rh catalyst with an inert substance, and then slowly adding a liquid glue solution dropwise during the mixing process to obtain a mixed material; 2) drying the obtained mixed material to obtain a dried catalyst; 3) Grind the dried catalyst fully, compress it into tablets using a tablet press, and pass it through a 20-40 mesh sieve to obtain a molded catalyst.

2. The molding method according to claim 1, characterized in that: In step 1), the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance are first mixed for 10-60 minutes, and then the liquid glue solution is added dropwise, and the mixing is continued for 0.5 to 2 hours, more preferably 1 to 1.5 hours; Preferably, the inert substance in step 1) is one or more of silicon powder, alumina and molecular sieve; Preferably, the mass of the inert substance in step 1) is 20 to 80 wt% of the total mass of the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance; Preferably, the liquid glue in step 1) is an aqueous solution selected from the following substances: one or more of polyvinyl alcohol, polyacrylate, polyalkyl acrylate, preferably polyvinyl alcohol, and the concentration is preferably 0.1-10wt%, more preferably 0.3-5wt%, more preferably 0.3-1.6wt%; Preferably, the weight average molecular weight of the polyvinyl alcohol is preferably 400 to 20,000, more preferably 1,000 to 15,000, and most preferably 5,000 to 10,000; Preferably, in the mixed material in step 1), the ratio of the mass of water to the total mass of the hyper-crosslinked phosphine ligand polymer Rh catalyst and the inert substance is (0.2-0.4):

1.

3. The molding method according to claim 1, characterized in that: The drying in step 2) is specifically: first drying at 20-50° C. for 12-36 hours, and then drying at 50-80° C. for 3-18 hours.

4. A molded super-crosslinked phosphine ligand polymer Rh catalyst obtained by the molding method according to any one of claims 1 to 3.

5. Use of the shaped hyper-crosslinked phosphine ligand polymer Rh catalyst according to claim 4 in catalyzing the hydroformylation of allyl acetate to prepare 4-acetoxybutyraldehyde in a fixed bed reactor.

6. The use according to claim 5, characterized in that: The catalyst is loaded after being diluted with porcelain balls, the volume percentage of the catalyst in the total loading is 70% to 90%, the inlet pressure of the reaction gas is 1-8Mpa, the reaction gas is a mixed gas of hydrogen and carbon monoxide, and the absolute volume space velocity of allyl acetate to the catalyst is 10 to 200h -1 , the inlet concentration of allyl acetate is 6% to 12% mol / L, the molar ratio of toluene to allyl acetate is 1 to 2, and the reaction temperature is 50 to 200°C.

7. The use according to claim 5, characterized in that: The fixed bed reactor is divided into three reaction zones from top to bottom: an upper section, a middle section and a lower section, the proportion of the catalyst increases successively, and the catalyst loading amounts of the three sections are in a weight ratio of 1:2:3.

Citation Information

Cited By

  • Tabletting method and mold for improving forming rate of catalyst

    CN121756650A